Alvin is in the Building Alvin Ailey American Dance Theater - Brennan, Mary (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Alvin Ailey American Dance Theater. PALABRAS CLAVE: Alvin Ailey, Clifton Brown, Judith Jamison, Stevie Wonder, Rennie Harris, Robert Battle, AAADT.